Estimation and Validation of Dietary Nitrate and Nitrite Intake in Iranian Population - Zahra BAHADORAN; Asghar GHASEMI; Parvin MIRMIRAN; Yadollah MEHRABI; Fereidoun AZIZI; Farzad HADAEGH (Tehran University of Medical Sciences, 2019)
Background: The aim of this study was calibration of a nitrate (NO3)/nitrite (NO2) database for estimated its dietary intakes. Methods: Overall, 250 healthy Tehranian adults were assessed in 2015 for dietary intakes of NO3 and NO2 and its serum and urine concentration. Food composition values for NO3 and NO2 were derived from a recent survey conducted on frequently consumed food items among Iranians. The correlation of dietary intakes of NO3/NO2 and its urinary and serum values was evaluated. Results: Mean (±SD) intakes of dietary NO3 and NO2 were 505±160 and 7.7±2.2 mg/d, respectively. The correlation coefficient of intake and urinary NO3 was 0.83 (95% CI=0.56-0.91) and 0.57 (95% CI=0.49-0.67) in men and women, respectively. A moderate agreement was also observed between NO2 intake and its urinary levels (r=0.27, 95% CI=0.13-0.37, and 0.29, 95% CI=0.17-0.41, in men and women, respectively). Conclusion: Using a national database of NO3 and NO2 content of food items along with a valid food frequency questionnaire could provide a valid estimation of dietary intakes of NO3 in the target population.